CCAC Paddy Rice Component: Highlights, Challenges, Lessons - Wollenberg, Eva Karoline; Nagano, Akiko; Sander, Björn Ole (2018)
CCAC Paddy Rice Component: Highlights, Challenges, Lessons Learnt, Opportunities (July 2017 – June 2018) July 10, 2018 Presentation by: Lini Wollenberg, CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Akiko Nagano, Environmental Policy Office, Ministry of Agriculture, Forestry and Fisheries (MAFF), Japan Björn Ole Sander, International Rice Research Institute (IRRI)